Leadership and Public Management: the Life Cycle of a Public Manager Mandate - Ysa, Tamyko; Salvador i Iborra, Susanna (Revista del CLAD Reforma y Democracia, 2015)
A growing body of literature identifies the impact of leader characteristics on the strategy and performance of organizations. This article, after reviewing the leadership literature, and, in particular, the public management literature regarding leadership and public managers, concludes that most of the literature on the effects of this leadership is static. To fill this gap and add a dynamic and longitudinal analysis, the paper applies the life cycle concept to the public managers’ mandate, a still under researched topic in the public management literature. First, the article focuses on the horizontal approach to public managers’ leadership along its mandate, in contrast to the traditional vertical approach analyzing promotions along a career. That is, the public manager’s life cycle. Second, this document identifies the key dimensions and phases along the public manager mandate’s life cycle, and develops the following proposals through a phase model: 1) Public managers at the beginning of their mandates focus on achieving the goals measured by indicators, with initial support from the political environment that appointed them. 2) In a second phase a period of exploration starts, allowed by some success, and the avoidance of political mistrust. 3) In the third phase the public manager selects the narrative by which it will be recognized its mandate in the organization. For that, the manager weaves internal information networks to develop a long-term vision for the organization. 4) In the convergence phase is when the maximum results are obtained by public managers, since an inverted U shape is shown between tenure and results. 5) The dysfunction phase or executive sclerosis, is when the manager’s power and the knowledge of the task is at its maximum. However, if the mandate does not have a limit on its duration, the consequences for the organization can be lethargy or crisis. Last but not least, the article builds an overarching research proposal, combining a survey based on recognized scales by the literature, and semi-structured interviews, to perform an exploratory analysis of the conceptual model and its propositions.